THE STRATEGY OF DISTANCE LEARNING AT SALAF BOARDING SCHOOL IN PANDEMIC COVID-19 - Khamid, Abdul; Rahmawati, Aida Dwi (Rabbani: Jurnal Pendidikan Agama Islam, 2021)
The purpose of this research to find out about strategies of distance learning (pjj) in PPTI Al-Falah Salatiga City in the situation of covid-19 outbreaks, the positive impact of implementing PJJ in PPTI Al-Falah Salatiga City, and inhibiting factors of PJJ implementation in PPTI Al-Falah Salatiga City. This research uses qualitative approach. Primary data is collected using google form and secondary data form related articles and literature. From these studies it is known, distance learning strategies utilize online technology as a learning media. The positive impacts include online learning activities, increasing the ability of students to utilize technology, and increasing the creativity of clerics and religious teachers. And the inhiting factors are the limitations of the internet network, the limited costs, and the limited facilities and infrastructure of the students in attending distance learning.